2014
DOI: 10.3141/2401-05
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Recementation Reactivity of Recycled Concrete Aggregate Fines

Abstract: The use of recycled concrete aggregate (RCA) as a drainage material in exfiltration trenches and base and subbase layers is becoming increasingly common. During crushing, stockpiling, transporting, and placing, however, RCA may produce fines that could recement and clog the pavement drainage system. Many previous studies indicated that not only the structural capacity but also drainage of pavement subsurface layers can be greatly affected by the properties and gradation of the aggregate used. This study evalua… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
7
0
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(10 citation statements)
references
References 19 publications
1
7
0
2
Order By: Relevance
“…Tests carried out by some researchers [22,23] have proved that recycled mortar contains non-hydrated cement, calcium hydroxide (CH) and dicalcium silicate (C 2 S), which are capable of hydration and creation of rehydration products. Some research has shown, however, that the mortar remaining on the surface of the recycled aggregates stored outside for a longer time does not show any rehydration reactivity [24]. Nevertheless, a study carried out by Vegas et al [25] of the mix proportions and characteristics of mortars made with recycled concrete aggregate showed that up to 25% recycled aggregate can be used in cement-based masonry mortars with no significant decline in performance and no new admixtures or higher cement content required.…”
Section: Introductionmentioning
confidence: 99%
“…Tests carried out by some researchers [22,23] have proved that recycled mortar contains non-hydrated cement, calcium hydroxide (CH) and dicalcium silicate (C 2 S), which are capable of hydration and creation of rehydration products. Some research has shown, however, that the mortar remaining on the surface of the recycled aggregates stored outside for a longer time does not show any rehydration reactivity [24]. Nevertheless, a study carried out by Vegas et al [25] of the mix proportions and characteristics of mortars made with recycled concrete aggregate showed that up to 25% recycled aggregate can be used in cement-based masonry mortars with no significant decline in performance and no new admixtures or higher cement content required.…”
Section: Introductionmentioning
confidence: 99%
“…This is probably due to hardened cement paste that adheres to the surface of aggregates. The XRD analysis found that calcite (CaCO 3 ), quartz (SiO 2 ), jennite (Ca 9 H 2 Si 6 O 18 (OH) 8 Á6H 2 O), and larnite (Ca 2 SiO 4 ) are the main mineral components of RCA, confirming that RCA mainly consists of hydrated cement, sand, and limestone (Nam et al 2014(Nam et al , 2015Kim et al 2014).…”
Section: Characterization Of Rcamentioning
confidence: 94%
“…A series of laboratory tests were performed to evaluate the basic physical properties of RCA such as specific gravity, unit weight (kg/m 3 ), and void content (%) (Table 1). X-ray diffractometer (XRD, Rigaku D/MAX XRD II) with CuKa radiation, 2 theta scanning from 5°to 80°with step size of 0.02°, was used for mineralogical investigation (Wagih et al 2013;Nam et al 2014Nam et al , 2015Kim et al 2014).…”
Section: Rca Preparation and Characterizationmentioning
confidence: 99%
See 1 more Smart Citation
“…According to the USEPA, total shingle waste generated in the U.S. is approximately 11 million tons per year [2]. Beneficial utilization of byproduct and waste materials in road construction have been made and it contributes to the success of sustainability [3][4][5][6][7][8][9][10][11][12][13][14]. It consists of roughly 90% representing post-consumer scrap (or tear-off shingles) and 10% comprising post-manufacture scrap [15].…”
Section: Introductionmentioning
confidence: 99%